The outer membrane protein A as a model for the study of lipid-protein interactions in complex neuronal membranes (2019)
Understanding the dynamics of different proteins with their lipidic environment can provide a great insight regarding the novel uses of this molecules in areas such as drug delivery systems. Here, a model for the study of the protein-lipid interactions of the OmpA protein of the Gram- negative bacteria Escherichia coli with a complex model of a neuronal membrane was studied. Our experimental setup allows the study of the lipid-protein interactions in a way that up to four proteins can be studied simultaneously. Cumulative histograms of specific lipid-protein interaction show differences between periplasmic and transmembrane domains, specifically the periplasmic domains shows high affinity for lipids containing a sugar group. We hope our simulations give insights into the mechanism by which magnetite-coated nanoparticles translocate mammalian membranes.